1985
DOI: 10.1111/j.1464-410x.1985.tb06426.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐treatment Fertility in Patients with Testicular Cancer.: II. Influence of Cis‐platin‐based Combination Chemotherapy and of Retroperitoneal Surgery on Hormone and Sperm Cell Production

Abstract: Active sperm production was observed in 20 of 35 patients with testicular cancer 1 year after discontinuation of all treatment (retroperitoneal surgery only: 13; cis-platin-based chemotherapy (CVB) +/- other treatment: 22). The percentage of patients who regained spermatogenesis increased slightly after a further 1 to 2 years. Fourteen patients (of 121 under observation) impregnated their wives (after retroperitoneal surgery: 9; after CVB +/- other therapy: 5). The individual serum FSH values correlated signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
4

Year Published

1988
1988
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 9 publications
2
15
0
4
Order By: Relevance
“…The effect of chemotherapy in the com partment inside of the blood-testis barrier was also dem onstrated in the specimens of contralateral biopsies that showed the same amount of germ cell damage (table 1). Moreover, many reports describe the deleterious effects of cytostatic chemotherapy on the intratubular germ cell layer [15,16] as evidenced by testicular biopsies [17], increased follicle-stimulating hormone levels [18,19] and impaired fertility [20].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of chemotherapy in the com partment inside of the blood-testis barrier was also dem onstrated in the specimens of contralateral biopsies that showed the same amount of germ cell damage (table 1). Moreover, many reports describe the deleterious effects of cytostatic chemotherapy on the intratubular germ cell layer [15,16] as evidenced by testicular biopsies [17], increased follicle-stimulating hormone levels [18,19] and impaired fertility [20].…”
Section: Discussionmentioning
confidence: 99%
“…Since most patients with testicular cancer are of a young age, the impact of therapy on sexual function and fertility has become increasingly important. Testicular cancer patients may have a reduced spermatogenesis ('hypospermia') at diagnosis (Hendry et al, 1983;Berthelsen and Skakkebaek, 1984;Cassileth and Steinfeld, 1987;Moynihan, 1987;Nijman et al, 1987;Fossa et al, 1988;Sleijfer et al, 1995) and after orchidectomy (Lampe et al, 1997), and only between 22 and 63% of patients fulfil the definition of normospermia at diagnosis (Hendry et al, 1983;Fossa et al, 1985;Nijman et al, 1987;Lampe et al, 1997). Three disease-associated conditions, local structural abnormalities detected by biopsy of the contralateral testis, the presence of sperm antibodies and endocrine factors, may be responsible (Berthelsen and Skakkebaek, 1984;Guazzieri et al, 1985).…”
mentioning
confidence: 99%
“…Several investigators have shown the time-dependent recovery of spermatogenesis in 60-80% of the patients treated with platin-based chemotherapy (Fosså et al, 1985b;Lampe et al, 1997). The preservation of patients' ejaculatory function thus becomes a major issue for maintenance of fertility.…”
Section: Discussionmentioning
confidence: 99%